Hitchcock's ear music and the director's art - Schroeder, David P. 1946- (Continuum, 2012)
Music is an underexplored dimension in Hitchcocks works. Taking a different view from most works on Hitchcock, David Schroeder focuses on how an expanded definition of music influences Hitchcocks conception of cinema. The structure and rhythm of his films is an important addition to the critical literature on Hitchcock and our understanding of his films and approach to filmmaking. Alfred Hitchcock liked to describe his work as a director in musical terms; for some of his films, it appears that he started with an underlying musical conception, and transformed that sense of music into visual ima